Heat Shock Proteins and Heat Shock Protein-Antibody Complexes in Placental Tissues - M. Ziegert; S. S. Witkin; I. Sziller; H. Alexander; E. Brylla; W. Härtig (Hindawi Limited, 1999)
Objective: The relationship between pregnancy outcome and expression of the heat shock proteins (hsps) or hsp-antibody complexes of 60kD (hsp60), 70kD (hsp70), and 90kD (hsp90) in placental tissue and circulating antibodies to hsps was evaluated.